Herpes Simplex Virus and Surgical Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs)
The presence of herpes simplex virus (HSV) was determined by polymerase chain reaction in surgical specimens from 50 patients (13 to 58 years of age) with epilepsy obtained from multiple centers, including the National Neurological Research Specimen Bank, West Los Angeles Veterans Affairs Medical Center, Los Angeles, CA.